Chemical composition of essential oil from lindera subumbelliflora kosterm and its effect on the susceptibility and biofilm activities of candida albicans and streptococcus mutans - Mohd Zain, Nur Nabilah; Wan salleh, Wan Mohd Nuzul hakimi; Arzmi, Mohd Hafiz; Salihua, Abubakar Siddiq; Ab Ghani, Nurunajah (Taylor & Francis, 2023)
the chemical composition of the essential oil of Lindera subumbel- liflora (Lauraceae) was investigated for the first time. the essential oil was obtained by hydrodistillation and fully characterised by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-mS). the antifungal activity of L. subumbelliflora essential oil was tested against Candida albicans and Streptococcus mutans using the broth microdilution assay, whereas the microbial biofilms were determined using a semi-quantitative static biofilm. a total of 28 components (99.6%) were successfully identified, which were characterised by β-eudesmol (14.6%), cis-α-bergamotene (11.0%), α-copaene (8.5%), dodecen-1-ol (8.5%), and (E)-nerolidol (8.3%). the essential oil exhibited activity against Candida albicans and Streptococcus mutans with miC values of 250 and 500 μg/mL, respectively. the essential oil increased the biofilm of Candida albi- cans by 38.25%, however, decreased the biofilm of Streptococcus mutans by 47.89% when treated with 500μg/mL. thus, the essen- tial oil has a promising application in dentistry via inhibition of the growth of Candida albicans and Streptococcus mutans. However, the antibiofilm activity of the essential oil is only applicable for cario- genic Streptococcus mutans.